Implementation of a Sustainable Ventilator-Associated Pneumonia Prevention Protocol in a Pediatric Intensive Care Unit in Managua, Nicaragua. Issue 6 (November 2016) - Chinnadurai, Kelsey; Fenlason, Lindy; Bridges, Brian; Espahbodi, Mana; Chinnadurai, Sivakumar; Blood-Siegfried, Jane
Abstract : Background: Ventilator-associated pneumonia (VAP) is a common nosocomial infection in pediatric intensive care units (ICUs). Ventilator-associated pneumonia protocols decrease the incidence of VAP; however, many components of these protocols are not feasible in all settings. This study was done in a large pediatric hospital in Nicaragua. Objective: The aim of this study is to implement a sustainable evidence-based VAP protocol, in a different culture, for the purpose of decreasing VAP rates. Methods: This quality improvement study used a bidirectional cohort design with the retrospective group as the control and the prospective group as the experimental population. A daily checklist monitored compliance to the implemented protocol in the prospective group. A 2-sided Fisher exact test compared the differences in VAP rates between the 2 populations. Results: During the 90-day implementation period, 123 ventilated patients in 3 separate ICU wings were evaluated, with 99 included in the final analysis. These data for 2014 were compared with the VAP rates recorded for the same time period in 2013. The highest adherence to the protocol was demonstrated by ICU wing 1, with a 90% decrease in VAP rates. No statistical difference in VAP rates was demonstrated by ICU 2, and ICU 3 demonstrated an increase in both patient acuity and VAP rates. Discussion: Implementation of a sustainable VAP protocol in a pediatric ICU in Nicaragua can reduce the incidence of VAP. Multiple barriers and challenges associated with implementation in a resource-constrained environment are discussed.